New Aboriginal hand stencil discoveries at the Freycinet National Park, Tasmania. Issue 1 (2nd January 2016) - Dix, Samuel
Abstract: Until the recording of hand stencils on the Derwent River near Meadowbank in 1958, the only rock markings known in Tasmania were those pecked in stone. Initially believed to be made by Aboriginal people from New South Wales brought to Tasmania, very little else was thought of the stencils until subsequent recordings challenged this theory and proved them to be a marking form in Tasmanian Aboriginal culture. The stencils of Fisheries Creek on the Freycinet Peninsula are different to those elsewhere in the state by virtue of their geographical location the material they were painted on, their state of preservation and the presence of associated archaeological deposits. However, this type of rock marking is rapidly deteriorating through natural erosion and many stencils may have gone unnoticed due to the opaque nature of their appearance. Applying Decorrelation Stretch (DStretch) techniques, six new hand stencils were recorded at Fisheries Creek in 2013, including two small faint stencils possibly indicating the presence of children at the site and during the art production. These recent discoveries indicate a need to update the recording practices of archaeologists in Tasmania when conducting archaeological surveys to represent better those rock art motifs that may not be visible to the naked eye.